The effectiveness of dragon fruit peel Hylocereus polyrhizus in feed on color quality and growth performance of comet fish Carassius auratus - Andriani, Yuli; Rihadatul Nabila, Shela; Intan Pratama, Rusky; Meyllianawaty Pratiwy, Fittrie; Hanidah, In In (Indonesian Society of Scientific Aquaculture (ISSA), 2025)
Color is a defining trait of ornamental fish, crucial for their aesthetic appeal, but it diminishes without pigment supplementation in their diet. Utilizing dragon fruit skin as a natural feed constituent offers a promising method to intensify fish coloration. This investigation aims to assess the impact of incorporating dragon fruit skin meal into fish feed on color vibrancy and growth performance, specifically focusing on comet fish. The test subjects, ranging from 4 to 6 cm in size and weighing 3.1 ± 0.2 grams, underwent examination. Employing a completely randomized design (CRD), the study involved four treatments replicated four times: treatment A (control), B (5% dragon fruit skin meal addition), C (10% addition), and D (15% addition). Before commencing the study, a preliminary assessment of dragon fruit skin meal was conducted, encompassing a chromameter-based color pigmentation test. Results revealed positive a (red) and b (yellow) values, a chroma value of 26.32 signifying carotenoid pigments, a hue value of 3.18° indicating a red-orange hue, and a moderate antioxidant activity was observed, indicating the presence of antioxidant compounds. Findings demonstrated that a 15% addition of dragon fruit skin meal substantially enhanced color vibrancy across the fish's body sections, including the head, body, and tail. Although fish weight and length were influenced by the feed amendment, ANOVA analysis did not ascertain significant effects. Furthermore, treatment C exhibited the most favorable feed conversion ratio and specific growth rate, recording values of 0.09 ± 0.03 and 0.934 ± 0.215, respectively. Keywords: comet fish, color brightness, dragon fruit peel flour ABSTRAK Warna merupakan ciri khas yang dimiliki oleh ikan hias, yang akan memudar bila tidak ada tambahan pigmen dalam pakan. Kulit buah naga dapat digunakan sebagai bahan pakan alami untuk meningkatkan kecerahan warna pada ikan. Riset ini bertujuan untuk mengetahui pengaruh pemberian tepung kulit buah naga dalam pakan terhadap kualitas warna dan performa pertumbuhan ikan komet. Ikan uji berukuran 4-6 cm dengan bobot 3,1 ± 0,2 gram. Metode riset yang digunakan yaitu metode eksperimental dengan menggunakan rancangan acak lengkap (RAL) yang terdiri dari 4 perlakuan dan 4 ulangan yaitu perlakuan A (kontrol), B (penambahan tepung kulit buah naga 5%), C (penambahan tepung kulit buah naga 10%) dan D (penambahan tepung kulit buah naga 15%). Sebelum penelitian dilakukan uji pendahuluan pada tepung kulit buah naga yaitu uji pigmentasi warna menggunakan chromameter diperoleh hasil nilai a positif (merah) dan b positif (kuning), nilai chroma 26,32 artinya terdapat kandungan pigmen karotenoid, nilai hue 3,18° menunjukkan warna orange merah, serta uji aktivitas antioksidan dengan hasil aktivitas antioksidan yang kurang aktif namun tetap memiliki kandungan antioksidan. Hasil riset menunjukkan bahwa penambahan tepung kulit buah naga 15% dalam pakan dapat meningkatkan kualitas warna yang optimal pada tubuh ikan yaitu kepala, badan dan ekor. Penambahan tepung kulit buah naga dalam pakan dapat mempengaruhi bobot dan panjang ikan namun di uji lanjut menggunakan analisis ANNOVA tidak memberikan pengaruh nyata. Penambahan tepung kulit buah naga juga memberikan nilai konversi pakan dan laju pertumbuhan spesifik terbaik pada perlakuan C dengan nilai 0,09 ± 0,03 dan 0,934 ± 0,215. Kata kunci: ikan komet, kecerahan warna, tepung kulit buah naga